Implementation of a modified sport programme to increase participation: Key stakeholder perspectives - Buszard, T.; Oppici, L.; Westerbeek, H.; Farrow, D. (Journal of Sports Sciences, 2020)
Modified sports, whereby equipment and rules are manipulated to facilitate skill performance, have been shown to promote skill learning and potentially increase participation. However, it is currently unexplored how key stakeholders - coaches and key figures working in National associations - who are critical stakeholders in implementing and delivering sport programmes, perceive modified sport. This study explored how tennis coaches and key figures working within tennis National associations perceived the impact of implementing a modified tennis campaign on participation and skill development in children and adults. Key figures and coaches around the world completed an online questionnaire. Both groups considered that modified tennis was positively associated with increasing and sustaining participation, skill learning, talent development and people`s attitude towards tennis. Furthermore, participants thought that a rule change (i.e., use of a low-compression ball in children competitions) and the campaign`s core messages (i.e., "serve, rally, score" and "easy, fun, and healthy") have been critical for the success of the campaign. These results support previous research on the positive impact of modified tennis on skill development and provide a further impetus on implementing modified sports to increase participation. Other sports can adopt similar strategies to improve their modified programmes.